Isolation and Identification Bacteria Species and Study Epidemiological Features to Burns Patients in Al- Yarmook Teaching Hospital (Indian Journal of Forensic Medicine & Toxicology, 2020)
The present study was conducted to identify the correlation between some epidemiological and bacterialcharacteristics of burn patients and their complications for the period from October to March 2018 forpatients who were visiting or staying at AL- Yarmook hospital. One hundred patients were randomly selectedafter being examined and diagnosed by a specialist. The pre-prepared questionnaire for the epidemiologicalfeatures of each patients, which included sex, age, marital or economic status, location of residence and thenature of the work of the patients was filled. While the bacterial side included the collection of skin swabsfrom areas exposed to burns (skin) and to all patients under sterile conditions and under the supervisions ofthe doctor supervisor the treatment of infected cases. Samples were transferred to the laboratory to completebacterial laboratory test. Samples were planted on the special and general culture, and bacterial growth wasobserved followed by final diagnosis of isolates. The results showed that the rate of infection was high infemales compare males (63% to 37%) respectively. While the incidence of burns was high in patients aged(16-30) 52%. The rate of infections was also high in patients with poor families (54%) while those living inrural areas had high rates of infection (41%).The results of primary bacterial transplantation gave a high positive result (78%). The total isolates obtainedfrom all initial transplant samples were 92% isolates and a percentage (117.9%), a high and satisfactoryrate. Gram negative bacteria isolates showed a higher frequency than gram positive (73.9) and (26.06%)respectively.It was noted that Pseudomonas spp was very high (48.9%) compared with rest of the positive or negativebacteria isolates, where the frequency presence of Klebsiella spp, Staphylococcus spp , StreptococcusSPP (25%), (18.4%), (7.6%) respectively. The results of the present study include the importance ofepidemiological aspects in the cases of burns, whether as factors that assist or are ready to be injured oraccelerated in the healing of the infected cases, in addition to the importance of early bacterial diagnosisof infection to control the complications of secondary infection of bacteria in cases of burns and thus easymedical treatment